Conjurverse : The Memory Thieves - Book 2 - Clayton, Dhonielle (New York : Henry Holt and Company, 2023)
In her second year at Arcanum Training Institute, Ella grapples with fame, unearths a perilous school secret, and faces a mysterious magical illness outbreak, prompting her, alongside Brigit and Jason, to clear her name, while working tirelessly to safeguard the Marvellian realm from impending chaos.
Keywords: African Americans -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Diseases -- Juvenile fiction; Secrecy -- Juvenile fiction; Fantasy -- Juvenile fiction; African Americans -- Fiction; Magic -- Fiction; Schools -- Fiction; Diseases -- Fiction; Secrets -- Fiction; Fantasy; Fantasy fiction; Novels